Persistence of the immune response at 5 years of age following infant immunisation with investigational quadrivalent MenACWY conjugate vaccine formulations - Khatami, A; Snape, MD; Davis, E; Layton, H; John, T; Yu, L; Dull, P; Gill, C; Odrjlin, T; Dobson, S; Halperin, SA; Langley, J; et al. (2012)
Background and aims: Serogroup A, C, W-135 and Y meningococcal (MenACWY) conjugate vaccines are recommended for routine adolescent immunisation in the United States and Canada. We evaluated the persistence of bactericidal antibodies through early childhood, following infant immunisation with varying schedules of MenACWY-CRM 197 vaccine. Methods: UK and Canadian infants were immunised with 2-3 doses of MenACWY-CRM 197 or 2 doses of serogroup C meningococcal (MenC) conjugate vaccine, and either MenACWY-CRM 197, 1/5 dose of MenACWY polysaccharide vaccine or no booster at 12 months. Control groups recruited at 60 months had received country-specific infant doses of MenC conjugate vaccine. hSBA titres were measured in participants at 40 and 60 months of age. Results: 382 children were enrolled in 12 groups (22-40 per group). By age 60 months, 3-11% of children primed and boosted with MenACWY-CRM 197 had hSBA titres≥1:8 against serogroup A, 14-45% against serogroup C, 57-85% against serogroup W-135 and 42-71% against serogroup Y. Children primed with MenC and boosted with MenACWY-CRM 197 had similar results, except for serogroup C (59%). In age-matched controls administered MenC vaccine at 2, 3, and 4 months (UK), 2 and 12 months or 12 months only (Canada), percentages with hSBA titres≥1:8 were 0-3%, 29-53%, 34-36% and 10-29% against serogroups A, C, W-135 and Y respectively. Conclusions: Serogroup-specific bactericidal antibody wane following infant immunisation with MenACWY-CRM 197, most markedly against serogroup A. Best persistence against serogroup C is observed with MenC conjugate vaccine priming and MenACWY-CRM 197 at 12 months, compared to schedules using only MenACWY-CRM 197, with the potential for providing broader protection compared to monovalent MenC vaccines alone. © 2012 Elsevier Ltd.